Complications of catheter ablation for atrial fibrillation in a high-volume centre with the use of intracardiac echocardiography - Aldhoon, Bashar; Wichterle, Dan; Peichl, Petr; Čihák, Robert; Kautzner, Josef (Europace, 2013)
AIMS: Catheter ablation (CA) for atrial fibrillation (AF) is a complex procedure that is associated with higher risk of complications. This study aimed at exploring the complication rate and corresponding risk factors in a high-volume centre with routine use of intracardiac echocardiography (ICE). METHODS AND RESULTS: In total 1192 consecutive AF ablation procedures (100% ICE-guided; 96.4% 3D-navigated; point-by-point radiofrequency ablation with open-irrigated tip catheter; 22.4% robotic navigation; 25.4% repeated ablation) were performed in 959 patients (aged 58 ± 9 years; 70.8% males; 35.9% persistent AF) between March 2006 and December 2010. Ablation endpoint in paroxysmal AF was complete electrical pulmonary vein isolation (PVI). Complex ablation was defined as PVI plus stepwise strategy for left atrial substrate ablation (43.5%) in persistent AF. Forty major complications (3.3%) during the procedure or within the 3 month follow-up were observed. No death or atrioesophageal fistula occurred. Three patients (0.25%) had cardiac tamponade/hemopericardium and five patients (0.42%) had cerebrovascular embolic event. Vascular injury was the most frequent (2.3%) complication. Low body weight was the only significant risk factor with 0.8% increase of complication rate per 10 kg of body weight decrease (P = 0.013). A trend for increase in complication rate was also observed for advanced age, female gender, and complex procedure. CONCLUSION: Atrial fibrillation ablation procedures guided by ICE in a high-volume centre are associated with low rate of serious complications. The composite risk score consisting of body weight, age, gender, and complexity of procedure predicted complications.
Keywords: hodnocení rizik; Comorbidity; Male; Postoperative Complications; retrospektivní studie; chirurgie s pomocí počítače; Risk Assessment; Česká republika; prevalence; Echocardiography; mužské pohlaví; Surgery, Computer-Assisted; pooperační komplikace; Catheter Ablation; echokardiografie; Atrial Fibrillation; komorbidita; Czech Republic; lidé; ženské pohlaví; Humans; Prevalence; Retrospective Studies; katetrizační ablace; Female; lidé středního věku; fibrilace síní; Middle Aged